PENINGKATAN KOMPETENSI GURU MELALUI STRATEGI KOLABORATIF : (PENELITIAN TINDAKAN MADRASAH DI MAN 8 PIDIE) - Armia Thaleb (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2022)
The development of increasingly sophisticated technology is the biggest challenge in the world of education today. The quality of education must be further improved so that students are able to master skills and compete globally. One of the spearheads in improving the quality of education to date is the role of teachers or educators in educating the nation's next generation. This study aims to describe the increase in teacher competence through collaborative strategies through action research Madrasas at MAN 8 Pidie. The research method used is action research. The results showed that there was an increase in teacher competence in implementing collaborative strategies which was evident in solving learning problems in class through discussion activities with teachers, starting from the planning, implementing, observing, and reflecting activities